The Australian Continent A Geophysical Synthesis - Kennett, Brian (ANU Press, 2018)
The Australian Continent: A Geophysical Synthesis is designed to provide a summary of the character of the Australian continent through the extensive information available at the continental scale, as a contribution to the understanding of Australia's lithospheric architecture and its evolution.The results build on the extensive databases assembled at Geoscience Australia, particularly for potential fields, supplemented by the full range of seismological information, mostly from The Australian National University. To aid in cross comparison of results from different disciplines, information is presented with a common projection and scales.